Perancangan dan Analisis Tegangan pada Desain Footrest Sepeda Motor Menggunakan Autodesk Inventor - Dhea Nuni Ananda; Rizal Hanifi; Aa Santosa (Politeknik Negeri Padang, 2021)
Motorbikes are widely chosen by the public as a mode of transportation in modern times, one of which is the automatic scooter type motorcycle. Visually, the matic scooter type motorcycle components have a nice and attractive shape, but this shape does not necessarily guarantee its safety. Not a few of these components have failed (broken) as happened to the footrest. Footrest is a component of a motorcycle vehicle that functions as a footrest for motorcycle passengers. Every different type of motorbike, the footrest shape is also different. The purpose of this study is to design a footrest design and analyze it with the help of software to obtain a footrest design that has a high safety factor value. The design of the motorcycle footrest design produces 3 different designs. The three designs were analyzed using the Autodesk Inventor 2017 software stress by providing a static load of 20 Kg and 90 Kg. From the analysis, the minimum safety factor value obtained from each footrest design against a load of 20 kg in design 1 is 13.42, design 2 is 5.7, and design 3 is 7.93. While the minimum safety factor value generated from each footrest design against a load of 90 kg in design 1 is 2.98, design 2 is 1.27, and design 3 is 1.76. Based on the results of the safety factor analysis carried out, the three designs are safe enough to withstand loads of 20 Kg and 90 Kg. But design 1 is safer because the resulting value of the safety factor is higher than the three designs, which is 2.98 to withstand a load of 90 Kg.